Arbitral Jurisdiction and Enforcement: Judicial Enforcement of Executive Title in Contract that Contains Arbitration Clause is Possible? - Pereira Giovanini, Ana Elisa Pretto (2017)
Currently prevails in Brazil the understanding that the arbitration court has national legal, and the award equates to the court judgment, considered judicial enforceable. Thus, with arbitration clause and clause containing enforceable efficiency within a legal business, it is analyzed whether it was necessary to resort to arbitration to have a sentence, or if the title could be executed directly in state court.